2021
DOI: 10.3390/ma14082037
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Mechanical Properties of Bis-GMA/TEGDMA Dental Composite Resins Enriched with Quaternary Ammonium Polyethylenimine Nanoparticles

Abstract: Modification of dental monomer compositions with antimicrobial agents must not cause deterioration of the structure, physicochemical, or mechanical properties of the resulting polymers. In this study, 0.5, 1, and 2 wt.% quaternary ammonium polyethylenimine nanoparticles (QA-PEI-NPs) were obtained and admixed with a Bis-GMA/TEGDMA (60:40) composition. Formulations were then photocured and tested for their degree of conversion (DC), polymerization shrinkage (S), glass transition temperature (Tg), water sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The DC, as well as S, increased from QAUDMA-8 to QAUDMA-14, indicating that the DC was a decisive factor in the volumetric contraction. Other important factors influencing S, such as differences in monomer molecular dimensions, shape, and hydrophilicity [32], appeared to be less significant. Interestingly, the results for the DC did not correlate to the results for the η and T g , which are commonly regarded as factors that determine the DC in dimethacrylate systems [30].…”
Section: Discussionmentioning
confidence: 84%
“…The DC, as well as S, increased from QAUDMA-8 to QAUDMA-14, indicating that the DC was a decisive factor in the volumetric contraction. Other important factors influencing S, such as differences in monomer molecular dimensions, shape, and hydrophilicity [32], appeared to be less significant. Interestingly, the results for the DC did not correlate to the results for the η and T g , which are commonly regarded as factors that determine the DC in dimethacrylate systems [30].…”
Section: Discussionmentioning
confidence: 84%
“…The development of antibacterial resin-based composites is one of the most important pathways of investigations regarding direct dental filling materials. In this study, QA-PEI-NPs synthesized with the previously described method 43 , 51 and characterized by an average size of 151 nm which was reported as optimal 43 were introduced into a representative bis-GMA-TEGDAM-UDMA matrix, finally compounded with two glass reinforcing fillers 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The QA-PEI-NPs were synthesized with the method described by by Youdovin-Farber et al 44 with additional specifications described in details by Barszczewska-Rybarek 43 . The poly(2-ethyl-2-oxazoline) (PEtOx) (Sigma Aldrich, St. Louis, MO, USA) was dissolved in distilled water in a flask equipped with a magnetic stirrer, thermometer and condenser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these in vitro studies revealed a high antibacterial effect over time. An increase in solubility and a decrease in mechanical properties such as flexural strength were observed with concentrations above 1% [ 12 , 13 , 14 ]. Few in-vivo studies have been conducted to test these materials intraorally with similar observations found regarding a high wide-spectrum antibacterial effect [ 15 ].…”
Section: Reviewmentioning
confidence: 99%